Environmental concentrations of copper and iron can alter the evolution of antimicrobial resistance of E. coli against ciprofloxacin and doxycycline - Sutradhar, Indorica; Kalyan, Prinjali; Chukwu, Kelechi; Abia, Akebe Luther King; Mbanga, Joshua; Essack, Sabiha; Hamer, Davidson H.; Zaman, Muhammad H. (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) is a global health challenge and there is increasing recognition of the role of the environment, particularly wastewater, in the development and spread of AMR. Although trace metals are common contaminants in wastewater, the quantitative effects of trace metals on AMR in wastewater settings remain understudied. We experimentally determined the interactions between common antibiotic residues and metal ions found in wastewater and investigated their effects on the development of antibiotic resistance in Escherichia coli over time. These data were then used to expand on a previously developed computational model of antibiotic resistance development in continuous flow settings to incorporate the effects of trace metals acting in combination with multiple antibiotic residues. We found that copper and iron, interact with both ciprofloxacin and doxycycline at wastewater relevant concentrations. This can significantly affect resistance development due to antibiotic chelation of the metal ions causing a reduction in the antibiotics’ bioactivity. Furthermore, modeling the effect of these interactions in wastewater systems showed the potential for metal ions in wastewater to significantly increase the development of antibiotic resistant E. coli populations. These results demonstrate the need to quantitatively understand the effects of trace metal-antibiotic interactions on AMR development in wastewater.